2013
DOI: 10.3945/ajcn.112.042523
|View full text |Cite
|
Sign up to set email alerts
|

Arginine appearance and nitric oxide synthesis in critically ill infants can be increased with a protein-energy–enriched enteral formula

Abstract: In critically ill infants with respiratory failure because of viral bronchiolitis, the intake of a PE-formula increases arginine availability by increasing arginine appearance, which leads to increased NO synthesis, independent of plasma arginine concentrations. This trial was registered at www.trialregister.nl as NTR515.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Plasma AA concentrations were determined by using liquid chromatographymass spectrometry (QTrap 5500 MS; AB Sciex) using internal standard method (12). Preparations of muscle tissue samples obtained from the vastus lateralis muscles at 180 and 420 min were performed as previously described (18).…”
Section: E75 Anabolic Responses To Increasing Protein Intake In a Mealmentioning
confidence: 99%
“…Plasma AA concentrations were determined by using liquid chromatographymass spectrometry (QTrap 5500 MS; AB Sciex) using internal standard method (12). Preparations of muscle tissue samples obtained from the vastus lateralis muscles at 180 and 420 min were performed as previously described (18).…”
Section: E75 Anabolic Responses To Increasing Protein Intake In a Mealmentioning
confidence: 99%
“…Arginine, citrulline kinetics and NO synthesis in the current eight critically ill children, were in the range of infants fed with standard nutrition in our previous study (29), which is to date the only study on arginine kinetics in fed critically ill children. Plasma amino acid concentrations of arginine and citrulline were however higher in that population than in the current one.…”
Section: Discussionmentioning
confidence: 77%
“…As previously reported, Gln and Pro are amino acids that are widely used in the production of Arg. Therefore, it is important that animals have significant levels of these two amino acids during the lactation period, since the milk is poor in Arg [2,25].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with Arg has been widely used in domestic animals to increase its presence in the blood, since it is a precursor of antioxidative compounds and polyamines for different functions [2,12]. It has been shown that supplementation with Arg can stimulate angiogenesis in the mammary gland of different animal species.…”
Section: Introductionmentioning
confidence: 99%